IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DESA SIOYONG KECAMATAN DAMPELAS KABUPATEN DONGGALA - Listiyawati, Listiyawati (Katalogis, 2017)
This study aimed to determine the implementation of Village Fund Allocation Policy in Sioyong Village Dampelas District Donggala Regency. This study used qualitative research method, where data and information were collected by using Likert scale instruments and interviews with selected informants. The results showed that the implementation of Village Fund Allocation Policy in Sioyong Village had already been well in general, but there were still many things that must be considered by the government of Sioyong Village, among them were the rural development programs should involve the villagers so that the implementation of Village Fund Allocation Policy run effectively and improve the quality of village apparatuses to be able to do the best services to the community of Sioyong Village. The capacities of human resources as the implementers of Village Fund Allocation Policy in the field of education were still low indeed, thus affecting their ability to identify and resolve problems quickly, but however, they had the abilities to encourage people. It should be considered that the achievement of the village development goals besides the availability of quality human resources should also be supported by adequate facilities to help village apparatuses in carrying out any tasks assigned by the leadership. Therefore, the Village Head should be able to provide adequate facilities for the achievement of Sioyong Village development goals.